A Neuropragmatic Comparison of English and Uzbek: Cultural and Cognitive Dimensions of Pragmatic Language Processing - Nazarova Munisa Sodiq qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the neuropragmatic features of English and Uzbek, focusing on how the human brain processes context-dependent meaning such as politeness, indirect speech acts, and culturally loaded expressions. Neuropragmatics, a subfield of neurolinguistics, studies the interface between language, cognition, and social behavior. While English has been widely studied in neuropragmatics using tools such as EEG and fMRI, research on Uzbek remains scarce. This paper presents a comparative overview of pragmatic strategies in both languages, drawing on existing neurocognitive studies in English and sociolinguistic data from Uzbek. It also proposes a framework for future empirical research combining neuroimaging with cross-cultural pragmatics. The findings suggest that while both languages rely on similar brain regions for pragmatic processing (e.g., prefrontal cortex, right hemisphere), cultural norms significantly shape how indirectness, politeness, and emotional tone are interpreted. This study highlights the need for more culturally inclusive research in neurolinguistics and opens avenues for experimental work on lesser-studied languages like Uzbek.